From Aktionsart to aspect: grammaticalization and subjectification in Greek - Amalia Moser (Acta Linguistica Hafniensia, 2014)
This article proposes an analysis of the historical changes in the aspectual system of Greek as a process of grammaticalization and subjectification, thus challenging the traditional view of Greek verbal aspect as a stable and in fact extremely conservative category, possibly very close to that of Proto-Indo- European. Specifically, the claim put forward here is that the original tripartite morphological opposition (Aorist – Present – Perfect stems) expressed Aktionsart, i.e. lexical aspect, distinctions (punctuality/telicity– durativity/atelicity–state, respectively) while the modern binary morpho- logical opposition (Aorist–Present stems) expresses the purely aspectual perfective–imperfective opposition. Since Aktionsart is based on inherent features of the action/state denoted by the verb while aspect expresses the speaker’s point of view, this constitutes a shift from objectivity to subjectivity as well as a somewhat atypical grammaticalization process. Keywords: gradient; perfective; progressive; habitual; perfect